Performance of maximum power point tracker in tropical climate - Mekhilef, Saad; Rahim, N.A.; Ping, H.W. (2006)
The performance of maximum power point tracker in tropical climate has been presented in this paper. The maximum power point tracker output voltage and current are used for control purposes, rather than for its input voltage and current. It is shown that using the output parameters simplifies the maximum power point tracker controller. Moreover, using this approach, only one out of the two output parameters needs to be sensed. where the proposed system configuration consist of commonly used dc/dc converter, which is applied for the power conversion stage of the tracker, an Xillinx FPGA acting as the controller, a ADC, PV array and three phase inverter which is connected to the grid. Method of locating the maximum power point (MPP) is based on hill climbing technique. An MPPT using a step up converter is developed its performance is compared under different solar irradiance and ambient temperatures. It showed an improvement in the output power by 18 (average) over a wide range or solar irradiation in a day.